2004
DOI: 10.1188/04.onf.e116-e126
|View full text |Cite
|
Sign up to set email alerts
|

Supportive Care Needs of Parents of Children With Cancer: Transition From Diagnosis to Treatment

Abstract: Although more research is required, supportive care that focuses on informational and emotional support appears to be most important from diagnosis to treatment. Using a conceptual framework such as the Supportive Care Needs Framework provides a methodology for planning care based on needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
87
1
23

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(116 citation statements)
references
References 43 publications
5
87
1
23
Order By: Relevance
“…They reported that parents had information needs especially on fertility and posttreatment challenges and the desire to receive the information in a written format, like an information booklet. Other studies assessed needs in a broader way and found that information need was the most prevalent unmet need [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…They reported that parents had information needs especially on fertility and posttreatment challenges and the desire to receive the information in a written format, like an information booklet. Other studies assessed needs in a broader way and found that information need was the most prevalent unmet need [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…In general, the treatment of childhood cancer negatively impacts the social and professional routines of parents, often requiring them to leave their jobs and give priority to treatment (Björk et al, 2005;Earle, Clarke, Eiser, & Sheppard, 2006;Kerr, Harrison, Medves, & Tranmer, 2004;Ljungman et al, 2003;McGrath, 2001;Steffen & Castoldi, 2006;Young et al, 2002). Attention totally focused on a child may lead to marital conflict, impair communication and/or the self-care of parents (Costa & Lima, 2002;James et al, 2002;Steffen & Castoldi, 2006).…”
Section: The Psychosocial Impact Of Childhood Cancer On Parentsmentioning
confidence: 99%
“…Access to information concerning the disease, the child's physical condition, procedures, benefits and side effects are stressed by the parents to be crucial over the course of the treatment (Ferreira, 2005;Kerr, Harrison, Medves, & Tranmer, 2004;Kerr, Harrison, Medves, Tranmer, & Fitch, 2007;Mendonça, 2007). The availability of social support from family members, friends, co-workers, and neighborhoods is also extremely important (Bayat et al, 2008;James et al, 2002;Kerr, Harrison, Medves, & Tranmer, 2004;McGrath, 2001;McGrath et al, 2005;Wijnberg-Williams et al, 2006).…”
Section: Psychosocial Distressmentioning
confidence: 99%
See 1 more Smart Citation
“…De modo geral, o tratamento do câncer pediátrico tem um impacto adverso sobre a rotina social e profissional dos pais, exigindo muitas vezes que deixem o emprego, dedicando mais atenção ao paciente em tratamento (Björk, Wiebe & Hallström, 2005;Cohn, Goodenough, Foreman & Suneson, 2003;Dockerty, Skegg & Williams, 2003;Kerr, Harrison, Medves & Tranmer, 2004;Steffen & Castoldi, 2006;Young, Dixon-Woods, Findlay & Heney, 2002). A atenção concentrada sobre o filho doente pode contribuir para gerar conflitos maritais e prejuízos à comunicação e autocuidado dos pais (Costa & Lima, 2002;James & cols., 2002;Steffen & Castoldi, 2006).…”
unclassified